Restorative justice and shoplifting: participant awareness of harm, decision-making, and recidivism - Wilson, Tyler Murphy, author; Unnithan, Prabha, advisor; Shelley, Tara O'Connor, advisor; Scott, Malcolm, committee member (Colorado State University. Libraries, 2013)
This thesis examines a sample of participants from 2008-2011 who have completed the Restorative Justice Program for Merchants, Community, and Young Shoplifters (RESTORE) in Larimer County, Colorado. The research utilizes pre and post survey data of participants' awareness of harm and decision-making concerning their crime, as well as socio-demographic characteristics and prior offending behavior. The goal of this research is to identify the possible associations between the aforementioned participant characteristics and cognitive changes in their harm and decision-making awareness. In addition, this study explores what may or may not indicate participants' likelihood of committing additional crimes after completing RESTORE. Furthermore, by inspecting youths caught shoplifting and their participation in RESTORE, this study provides recommendations about programmatic practices and notes the limitations of the research. An examination of the data verifies that additional research is necessary to better identify how restorative justice principles can prevent a youths from future criminal behavior.
Keywords: diversion; shoplifting; restorative; community; crime; juvenile